2008
DOI: 10.1007/s00382-008-0501-8
|View full text |Cite
|
Sign up to set email alerts
|

The CLIVAR C20C project: which components of the Asian–Australian monsoon circulation variations are forced and reproducible?

Abstract: A multi-model set of atmospheric simulations forced by historical sea surface temperature (SST) or SSTs plus Greenhouse gases and aerosol forcing agents for the period of 1950-1999 is studied to identify and understand which components of the Asian-Australian monsoon (A-AM) variability are forced and reproducible. The analysis focuses on the summertime monsoon circulations, comparing model results against the observations. The priority of different components of the A-AM circulations in terms of reproducibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 60 publications
3
66
0
1
Order By: Relevance
“…It is better than the conventionally used sea level pressure (SLP) difference index across East Asia and North Pacific such as Guo et al (2003) in describing the monsoontropical Pacific connections. Specifying SST to an AGCM generally shows poor performance in reproducing the SLP response over the North Pacific and the associated changes of SLP difference index (Zhou et al 2008d). This deficiency is also seen in our model results as evidenced by the spurious anticyclone over the North Pacific (cf.…”
Section: Discussionmentioning
confidence: 99%
“…It is better than the conventionally used sea level pressure (SLP) difference index across East Asia and North Pacific such as Guo et al (2003) in describing the monsoontropical Pacific connections. Specifying SST to an AGCM generally shows poor performance in reproducing the SLP response over the North Pacific and the associated changes of SLP difference index (Zhou et al 2008d). This deficiency is also seen in our model results as evidenced by the spurious anticyclone over the North Pacific (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that climate models have limited skill in simulating and predicting the precipitation in terms of both climatological mean state and interannual variations (Chen et al 2010;Zhou et al 2009b). In contrast, the variability of East Asian monsoon circulation is well captured (Zhou et al 2009c;Song and Zhou 2014a). A successful reproduction of the interannual EASM pattern depends highly on the Indian Ocean-western Pacific anticyclone teleconnection (Kim et al 2012;Song and Zhou 2014a,b).…”
Section: F East Asiamentioning
confidence: 99%
“…The applied convection scheme has been checked in previous studies (e.g., Tost et al 2006;Kucharski et al 2009;Zhou et al 2009b). Zhou et al (2009b) evaluated the performance of various climate models including SOCOL (with mass-flux convection scheme) for Asian-Australian monsoon circulation indices and found that the Webster-Yang-Index, Indian Monsoon Index, Western North Pacific monsoon index, Australian monsoon index, and East Asian monsoon meridional wind index for ensemble mean of 9 SOCOL realizations are significantly positively correlated with observations (CC: ~0.58, ~0.36, 0.37, 0.32, and 0.60 respectively, see, Fig. 3 in Zhou et al 2009b).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Zhou et al (2009b) evaluated the performance of various climate models including SOCOL (with mass-flux convection scheme) for Asian-Australian monsoon circulation indices and found that the Webster-Yang-Index, Indian Monsoon Index, Western North Pacific monsoon index, Australian monsoon index, and East Asian monsoon meridional wind index for ensemble mean of 9 SOCOL realizations are significantly positively correlated with observations (CC: ~0.58, ~0.36, 0.37, 0.32, and 0.60 respectively, see, Fig. 3 in Zhou et al 2009b). Kucharski et al (2009) used the SOCOL model (with mass-flux convection scheme) for simulating the Indian summer monsoon variability on inter-annual to decadal timescale under the CLIVAR C20C project.…”
Section: Model Descriptionmentioning
confidence: 99%